Fcγ receptor binding is required for maximal immunostimulation by CD70-Fc - Dadas, Osman; Allen, Joel D.; Buchan, Sarah L.; Kim, Jinny; Chan, H. T. Claude; Mockridge, C. Ian; Duriez, Patrick J.; Rogel, Anne; Crispin, Max; Al-Shamkhani, Aymen (Frontiers in Immunology, 2023)
T cell expressed CD27 provides costimulation upon binding to inducible membrane expressed trimeric CD70 and is required for protective CD8 T cell responses. CD27 agonists could therefore be used to bolster cellular vaccines and anti-tumour immune responses. To date, clinical development of CD27 agonists has focussed on anti-CD27 antibodies with little attention given to alternative approaches. Here, we describe the generation and activity of soluble variants of CD70 that form either trimeric (t) or dimer-of-trimer proteins and conduct side-by-side comparisons with an agonist anti-CD27 antibody. To generate a dimer-of-trimer protein (dt), we fused three extracellular domains of CD70 to the Fc domain of mouse IgG1 in a 'string of beads' configuration (dtCD70-Fc). Whereas tCD70 failed to costimulate CD8 T cells, both dtCD70-Fc and an agonist anti-CD27 antibody were capable of enhancing T cell proliferation in vitro. Initial studies demonstrated that dtCD70-Fc was less efficacious than anti-CD27 in boosting a CD8+ T cell vaccine response in vivo, concomitant with rapid clearance of dtCD70-Fc from the circulation. The accelerated plasma clearance of dtCD70-Fc was not due to the lack of neonatal Fc receptor binding but was dependent on the large population of oligomannose-type glycosylation. Enzymatic treatment to reduce the oligomannose-type glycans in dtCD70-Fc improved its half-life and significantly enhanced its T cell stimulatory activity in vivo surpassing that of anti-CD27 antibody. We also show that whereas the ability of the anti-CD27 to boost a vaccine response was abolished in Fc gamma receptor (FcγR)-deficient mice, dtCD70-Fc remained active. By comparing the activity of dtCD70-Fc with a variant (dtCD70-Fc(D265A)) that lacks binding to FcγRs, we unexpectedly found that FcγR binding to dtCD70-Fc was required for maximal boosting of a CD8 T cell response in vivo. Interestingly, both dtCD70-Fc and dtCD70-Fc(D265A) were effective in prolonging the survival of mice harbouring BCL1 B cell lymphoma, demonstrating that a 2 substantial part of the stimulatory activity of dtCD70-Fc in this setting is retained in the absence of FcγR interaction. These data reveal that TNFRSF ligands can be generated with a tunable activity profile and suggest that this class of immune agonists could have broad applications in immunotherapy.